Reef Fish Abundance and Diversity at Marine Protected Area Gili Sulat and Gili Lawang, East Lombok, West Nusa Tenggara - Putra, Nyoman Widi Artha; Paryono, Paryono; Jefri, Edwin (Jurnal Biologi Tropis, 2024)
Gili Sulat and Gili Lawang have the potential to become a source of livelihood for the community due to their high biodiversity, where these two small islands can be used as a place for fisheries and ecotourism development. However, in West Nusa Tenggara itself there is still widespread destructive fishing which can affect the abundance of reef fish. Therefore, this research focuses on assessing the diversity and abundance of reef fish in the waters of Gili Sulat and Gili Lawang, Sambelia District, East Lombok Regency. This research was conducted from November 2023 to February 2024. Reef fish abundance data was collected using the UVC (Underwater Visual Census) method. The research results showed that there were 76 species, 38 genera and 16 families of reef fish in total at the six observation stations. The largest number of reef fish individuals is in the Pomacentridae family with 1180 individuals (0.79 ind/m2). The highest biomass of herbivorous fish and target fish is found in the Gili Sulat Sustainable Fisheries Zone, namely 2312.72 gr/m2, followed by the Gili Lawang Core Zone with a biomass value of 1221.32 gr/m2, while the Gili Lawang Utilization Zone has the lowest biomass value among all observation station.